THE Education Based on the Concept of Health Belief Model Effectively Increases Cervical Cancer Screening Rates in Women of Fertilizing Age - Musripah, Musripah; Nurhayati, Nurhayati (Indonesian Journal of Global Health Research, 2024)
Cervical cancer cases in Indonesia are increasing, therefore it is necessary to pay attention to preventive measures and early detection of cervical cancer in women of fertilizing age. The low awareness of women of of fertilizing age to carry out early detection through screening with IVA tests is one of the causes of increasing cases of cervical cancer in Indonesia. Therefore, researchers use an educational method based on the Health Belief Model (HBM) for women of fertilizing age.. The aim of this research is to increase cervical cancer screening rates with IVA tests after providing education based on the Health Belief Model (HBM). The method in this research uses quantitative methodology. The sample in this study amounted to 37 respondents. This research was conducted in Karang Anyar Village, Sawah Besar. The results were obtained (p value <0.001), with the results of the X² continuity correction analysis showing that HBM-based education increased screening rates by 18 times. The conclusion is that the education method using the Health Belife Model for women of fertilizing age can increase cervical cancer screening rates.